If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -1g = 6 Solving 15 + -1g = 6 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -1g = 6 + -15 Combine like terms: 15 + -15 = 0 0 + -1g = 6 + -15 -1g = 6 + -15 Combine like terms: 6 + -15 = -9 -1g = -9 Divide each side by '-1'. g = 9 Simplifying g = 9
| -6+3(-8x+1)=15 | | 3(f-8)=-24 | | .04m=.08 | | 5t(10-3t)= | | 7/x-4=14/6 | | -5(4x-1)=-3x-6 | | 7-k=5 | | -7x-13+9x-19=-4 | | -1=2(j-8)+1 | | 10(s-6)=-146 | | 32-4x=18-6x | | 10y^2+90y=0 | | H=15t-4.9t^2+3 | | -2(8x+3)=3x | | 4x-x=7squared | | 2n-8+6n=-14+8n | | 2z-15+3z=5-5z+10 | | 4(b-12)+1=17 | | 2x+32=60 | | 11+3x=15+9x-3x | | 2(m+1)+2=10 | | X-5x=6-2x+5 | | -24x+18=4 | | 3v+6=0 | | -7+x=7+9-5 | | -16=5v+11 | | 9x+6=3(x-4) | | -6+7k=1+7k | | 0.2x-1.6=2.4x+2.7 | | -8w+4=0 | | 2(r+7)=-4 | | 4m-3n=8form |